Power by Rotation - Van Zanten, Leonard (JOURNAL OF ADVANCES IN PHYSICS, 2020)
This essay is another journey in the magnetic nature of fundamental movement with emphasis on how and why magnets are attracted and repelled from one another. And the relation of how movement for its mode and direction comes to so many different outcomes. And a rehearsal in how and by what we come to interpret movement into all that exists for us.